Patient Access and User Experience in EHR/EMR Research: A Bibliometric Analysis (2018–2023) - Yuniarto, Mohammad Isa; Hidayah, Nur; Rosa, Elsye Maria; Reiniatie, Archie (Universitas Muhammadiyah Yogyakarta, 2026)
Patient access and user experience are increasingly central to the adoption and evaluation of electronic health records (EHR/EMR). This study maps global research trends on patient access and user experience in EHR/EMR research using a Scopus-based bibliometric approach. A total of 236 Scopus-indexed articles published between 2018 and 2023 were analyzed with VOSviewer to describe publication trends, leading countries and affiliations, authorship patterns, and keyword co-occurrence structures. The results showed sustained research activity across the period, with the highest publication output in 2018 and major contributions from the United States, Sweden, and the United Kingdom. Keyword co-occurrence indicates dominant themes related to patient portals, technology, and survey-based evaluations, reflecting an emphasis on access mechanisms, usability, and user perceptions. Network mapping further identifies clustered topics around portal-enabled access, technology integration, and experience assessment through surveys and interviews. Overall, the findings characterize the field's thematic structure and provide a basis for interpreting how patient access and user experience have been studied in EHR/EMR research.